Lamb wave dispersion in a PZT/metal/PZT sandwich plate with imperfect interface - Kurt, Ilkay; Akbarov, Surkay D.; Sezer, Semih (TAYLOR & FRANCIS LTD, 2016)
The Lamb wave dispersion in a PZT/Metal/PZT sandwich plate is investigated by employing the exact linear equations of electro-elastic waves in piezoelectric materials within the scope of the plane-strain state. It is assumed that at the interfaces between the piezoelectric face layers and metal core layer, shear-spring and normal-spring type imperfect conditions are satisfied. The degree of this imperfectness is estimated through the corresponding shear-spring and normal-spring type parameters which appear in the contact condition characterizing the transverse and normal displacements' discontinuity. The corresponding dispersion equation is derived, and as a result of the numerical solution to this equation, the dispersion curves are constructed for the first and second lowest modes in the cases where the material of the face layers is PZT and the material of the middle layer is Steel (St). Consequently, for the PZT/St/PZT sandwich plate, the study of the influence of the problem parameters such as the piezoelectric and dielectric constants, layer thickness ratios, non-dimensional shear-spring, and normal-spring type parameters, is carried out. In particular, it is established that the imperfectness of the contact between the layers of the plate causes a decrease in the values of the wave propagation velocity.
Keywords: PROPAGATION; Physics